Penatalaksanaan disgnati kelas II skeletal dengan bilateral sagital split osteotomy - Muhammad Ruslin; Ida Ayu Astuti; D. Bram Tuinzing (Journal of Dentomaxillofacial Science, 2010)
This case reported a female patient aged 30 years was treated with orthognathysurgery in Hasan Sadikin Hospital, Bandung. Based on clinical and radiologicalexaminations, model study and photography, diagnosis of skeletal dysgnathy class IIwas established. The orthodontic treatment is a preparation before surgical operationto achieve stability in optimal dental interdigitation. In operation, BSSO, chinplasty,and V-Y plastic upper lip as well as intermaxillary fixation (IMF) ligation was carriedout at the dentofacial position class I. At day-16, radiography was carried out toevaluate the surgical outcome and the bone position. At day-21, the opening of jawswas 1.5 cm; and at day-42, the patient was reconsulted to orthodontist, and tophysical medicine and rehabilitation In month-3, occlusion, facial profile andharmony, and jaw functions showed the satisfying outcome, though for theinterdigitation stabilization, the rubber elastics was still installed.